An Analysis Of The Influence Of Digital Accounting System Integration And Financial Literacy On The Financial Performance Of MSMES In The Era Of Industry 4.0 - Martina, Sri; Girsang, Christin Imelda (Jurnal Ilmiah Accusi, 2025)
This study examines the influence of digital accounting system integration and financial literacy on the financial performance of MSMEs in the era of Industry 4.0. The central issue lies in the underutilization of digital technology and the low financial literacy levels among MSME actors. The aim of this research is to analyze the extent to which these two variables affect financial performance. This study employs a descriptive quantitative method through a survey conducted among selected MSME participants. Data were collected via questionnaires and analyzed using SmartPLS. The findings reveal that the digital accounting system exerts a dominant influence, while financial literacy also contributes significantly. This research highlights the critical role of integrating technology and financial education in fostering sustainable financial performance for MSMEs